Rituals During Lockdown : The "Clap for our Carers" Phenomenon in France - Nanta Novello Paglianti (Culture e Studi del Sociale, 2020)
The article will analyse the emergence of the applause for health workers to health personnel, a practice widespread in France since the first day of lockdown. We examine the meaning of this ritual that was first promoted on the web and then adopted by the social actors themselves in the semi-private space of windows and balconies. We will investigate the relationships and the meaning of this practice both on the web and in the social space.